Analysis of The Influence of Customer Satisfaction, Experiental Marketing and E-Service Quality on Loyalty of KAI Commuter Customers - Erna Indriastiningsih; Vivid Violin; Muhammad Syafri; Rezky Nurbakti; Loso Judijanto (SEULANGA SYSTEM PUBLISHER, 2023)
The goal of this study is to ascertain whether customer satisfaction, service quality, and experiential marketing directly affect consumer loyalty. People who commute by train are participants in this study. This study used a non-probability sampling technique called purposeful sampling, which had a sample size of 100 participants. The data analysis method used in this study is called path analysis. The study's findings show a definite correlation between customer satisfaction and the variable of service quality. Experiential marketing has a direct impact on customer satisfaction. Service excellence and experience marketing elements have a direct impact on customer satisfaction. Service quality has a direct bearing on customer loyalty. The experience marketing factor has a direct effect on customer loyalty. client happiness has a direct bearing on client loyalty. Service excellence, experiential marketing, and customer satisfaction all have a direct bearing on customer loyalty. The service quality factor indirectly influences customer loyalty by influencing client satisfaction. The experiential marketing element indirectly influences customer loyalty by influencing client satisfaction.